MODEL e-GOVERNMENT PEMERINTAHAN DESA - Watrianthos, Ronal; Nasution, Ade Parlaungan; Syaifullah, Muhammad (Universitas Komputer Indonesia, 2019)
E-Government development has become the government commitment as established in the Inpres 3/2003 concerning about the National E-Government Development Policy and Strategy. However, this government policy has not been fully implemented in local government, resulting the e-Government role as the pledge of the government that cannot run well. Resistance to change is one of the inhibiting factors in e-Government development. The Law No. 6 of 2014 about Villages states that the implementation of village governance by utilizing Information Technology can be done through e-Government Villages. An in-depth study of models suitable for e-Government villages is needed. The process of identifying the Village e-Government needs is carried out with a Critical Success Factor (CSF) analysis. The results of the analysis produce four stages of the model which are divided into dimensions of technological complexity and organization with the level of data and information integration. Whereas the results of portfolio futures from the development of this model using McFarlan's Analyst Grid so that strategic modules, high potential, support, and operational key can be elaborated. Key words: e-Government, CSF, Village